Continuing Professional Development: Reflective Practice Enhances The Competencies Of The English Language Teachers - K. Poornimavaralakshmi , M. Shanmugathai (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Continuing Professional Development is the need of the hour, as it helps the teachers to improve their standard of teaching both professionally and personally. Indeed, it is focused and planned in all the sectors apart from the educational sector. CPD has followed many frameworks like Conference, Workshops, FDP, In-Service Training, Pre-Service Training, Peer Review, Reflective Practices etc., in order to enhance the teaching competencies of the teachers. Among them, Reflective Practice acts as the best practice for the professional development of the English Language Teachers.It helps the teachers to do self-analysis of their own act of teaching in the classroom. Also, it encourages the teachers to find their own solution through self-observation or peer- observation. So, this study suggests the need of Reflective Practice in ELT classes as it meets the needs of both teachers and students in the classroom..